Cost-effectiveness assessment of liquid biopsy for early detection of lung cancer in Brazil - Kátia Marie Senna; Ivan Ricardo Zimmermann; Márcia Gisele Santos da Costa; Bernardo Rangel Tura; José Ronyeryson dos Santos Evangelista; Marisa Santos (PLoS ONE, 2025)
Introduction Lung cancer has a low survival rate due to late diagnosis, with most cases detected at advanced stages. Liquid biopsy, a non-invasive alternative to tissue biopsy, has emerged as a potential screening tool for early lung cancer detection. This study evaluates the cost-effectiveness of liquid biopsy screening using an autoantibody test (EarlyCDT-Lung®) in high-risk populations from the perspective of the Brazilian Unified Health System (SUS). Methods A decision-analytic model was developed, combining a decision tree and a Markov model to compare two strategies: standard clinical diagnosis without screening and liquid biopsy screening followed by confirmatory diagnostics. Model inputs included test accuracy, treatment costs, and survival data derived from systematic reviews, national registries, and published economic evaluations. The primary outcome was the incremental cost-effectiveness ratio (ICER) per quality-adjusted life year (QALY). Sensitivity analyses assessed model robustness. Results Liquid biopsy screening analysis of a hypothetical cohort of 1,000 individuals at high-risk of lung cancer resulted in an incremental cost of $ 570,120 and an incremental effectiveness of 7.56 QALYs, with an ICER of $ 75,435.63 per QALY gained. This result has far exceeded the willingness-to-pay threshold in Brazil ($ 7,017.54–21,052.62/QALY). Therefore, in case of assuming no significant cost reductions or accuracy improvements, the strategy would only become cost-effective in contexts where lung cancer prevalence exceeds 4.0%. Probabilistic sensitivity analysis confirmed a low likelihood of cost-effectiveness, even with varying test sensitivity, lung cancer prevalence, and cost assumptions. Discussion The adoption of an autoantibody test as a liquid biopsy for early lung cancer screening in high-risk populations in Brazil led to increased costs and was not considered cost-effective under the thresholds commonly applied in the Brazilian context.